The Utilization of Blockchain Technology to Enhance Data Security - Alif Sabilla Rustam Sutoto, Karomah; Sadewa, Ifan; Romadhona, Harri; Ridwan, Ridwan (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
The way governments and businesses operate globally is changing due to the worldwide trend of digital transformation. By implementing blockchain technology to improve data security in day-to-day operations, Indonesia's government and private sector are hastening the country's digital transition. Numerous blockchain initiatives, including payment systems, medical data storage, and certificate verification and validation, have been implemented in Indonesia. Notwithstanding, there are still a number of obstacles that Indonesia must overcome before it can effectively use blockchain technology, including imprecise legislation, inadequate infrastructure, and a dearth of knowledge about the network. Consequently, for Indonesia to adopt blockchain technology more quickly, assistance from all parties is required. In order to maximize blockchain technology's potential and hasten Indonesia's digital revolution, more research and development should be done.